Notch signaling in stomach epithelial stem cell homeostasis - Kim, Tae-Hee (The Rockefeller University Press, 2011)
The mammalian adult gastric epithelium self-renews continually through the activity of stem cells located in the isthmus of individual gland units. Mechanisms facilitating stomach stem and progenitor cell homeostasis are unknown. Here, we show that Notch signaling occurs in the mouse stomach epithelium during development and becomes restricted mainly to the isthmus in adult glands, akin to its known localization in the proliferative compartment of intestinal villi. Using genetic and chemical inhibition, we demonstrate that Notch signaling is required to maintain the gastric stem cell compartment. Activation of Notch signaling in lineage-committed stomach epithelial cells is sufficient to induce dedifferentiation into stem and/or multipotential progenitors that populate the mucosa with all major cell types. Prolonged Notch activation within dedifferentiated parietal cells eventually enhances cell proliferation and induces adenomas that show focal Wnt signaling. In contrast, Notch activation within native antral stomach stem cells does not affect cell proliferation. These results establish a role for Notch activity in the foregut and highlight the importance of cellular context in gastric tumorigenesis.